Serpocaulon tayronae (Polypodiaceae), a new species from the Sierra Nevada de Santa Marta, Colombia - Sanín, David (Phytotaxa, 2015)
Serpocaulon tayronae is described as a new endemic fern species from the Sierra Nevada de Santa Marta, Colombia. This species has long-creeping rhizomes, whitish or light-coloured patent scales, free veins and spores with dense rounded verrucae. In this aspect it resembles the species Serpocaulon eleutherophlebium, S. obscurinervium and S. patentissimum, as well as the species complexes of Polypodium plesiosorum and P. dulce. However it differs from these taxa by the clathrate orange rhizome scales and the pectinate laminae, proximally reduced with its pinnae slightly ascending. A key to the Colombian species of Serpocaulon is provided to distinguish the new species from the other taxa.